God Loves Uganda - Ross, Roger (United States, 2013)
A powerful exploration of the evangelical campaign to infuse African culture with values imported from America's Christian Right. The film follows American and Ugandan religious leaders fighting sexual immorality and missionaries trying to convince Ugandans to follow biblical law.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films